1990
DOI: 10.1002/jbmr.5650050807
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral loss and recovery after 17 weeks of bed rest

Abstract: The purpose of this work was to determine the rate and extent of bone loss and recovery from long-term disuse and in particular from disuse after exposure to weightlessness. For this purpose, bed rest is used to simulate the reduced stress and strain on the skeleton. This study reports on the bone loss and recovery after 17 weeks of continuous bed rest and 6 months of reambulation in six normal male volunteers. Bone regions measured were the lumbar spine, hip, tibia, forearm, calcaneus, total body, and segment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
222
0
9

Year Published

1996
1996
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 649 publications
(242 citation statements)
references
References 9 publications
11
222
0
9
Order By: Relevance
“…Calcium excretion was 74% higher. Disregarding a potential additional positive effect of the low-salt diet on bone, immobilization itself led to an increase in bone resorption of 24% (preambulatory phase to intervention with low NaCl) during low salt intake and HDBR, as stated by other authors previously (4,21,37,42,60). Most notably, the effect of the high salt intake in HDBR-an increase in one bone resorption marker (CTX) of 76% (preambulatory to intervention with high NaCl)-seems to have been much more pronounced than the effect of immobilization itself and highlights the importance of diet for immobilized persons, space travelers, and people with a sedentary lifestyle.…”
Section: Discussionmentioning
confidence: 59%
“…Calcium excretion was 74% higher. Disregarding a potential additional positive effect of the low-salt diet on bone, immobilization itself led to an increase in bone resorption of 24% (preambulatory phase to intervention with low NaCl) during low salt intake and HDBR, as stated by other authors previously (4,21,37,42,60). Most notably, the effect of the high salt intake in HDBR-an increase in one bone resorption marker (CTX) of 76% (preambulatory to intervention with high NaCl)-seems to have been much more pronounced than the effect of immobilization itself and highlights the importance of diet for immobilized persons, space travelers, and people with a sedentary lifestyle.…”
Section: Discussionmentioning
confidence: 59%
“…It has been hypothesized that fractures in vertebral bodies occur because of an increased load on the spine cause by contraction of paraspinal muscles. 16,22,23 It has been suggested that approximately 30% of compression fractures in patients with severe osteoporosis occur while the patient is in bed. 24 27 Patients with multiple compression fractures and progressive loss of vertebral body height may develop excessive thoracic kyphosis and lumbar lordosis.…”
Section: Presentation and Complications From Vertebral Compression Frmentioning
confidence: 99%
“…In addition, it has been reported that bone mineral density decreases 0.25% to 1.00% per week in patients who are on bed rest. 23,40 To reduce pain and thus promote early mobilization with conservative management, appropriate analgesics should be prescribed. Narcotics should be reserved for patients who receive inadequate relief from regular analgesics.…”
Section: Nonsurgical Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…When lost bone can be completely recovered following disuse, the required remobilization time is 2-3 times longer than the length of the disuse period because the rate of bone loss during inactivity is 2-3 times greater than the rate of bone recovery during remobilization [14,17,18]. However, bears in northern climates experience annual periods of disuse (hibernation) and activity that are approximately equal in length (6 months), yet black bear (Ursus americanus) cortical bone does not suffer any detrimental mechanical or structural consequences with age despite these relatively short recovery periods [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%